Analysis of Student’s Arabic Reading Pronunciation Characteristics on Discourse Text - Utami, Sri Nabilah; Nurbayan, Yayan; Maulani, Hikmah (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
Based on the importance of pronunciation in Arabic, this study aims to analyze the pronunciation characteristics of students' reading Arabic texts in the discourse text "مَدْرَسَتِيْ" and identify the factors of difficulty and causes of students' pronunciation errors. The research method used is descriptive with a qualitative approach. In this study, data collection was carried out by researchers by conducting observations, questionnaires, and interviewing students and Arabic teachers in one of the schools located in the city of Bandung. This research was conducted using test and non-test instruments. The test instrument used was to conduct a reading test of Arabic texts on students to see the characteristics of students' pronunciation in Arabic text readings. The non-test instruments are observation, questionnaires, and interviews. The results of this study indicate that the characteristics of students in reciting Arabic text readings are different and there are several errors from students when reading Arabic texts in one of the discourses in the tenth grade of senior high school Arabic textbook entitled "مَدْرَسَتِيْ". These errors are errors in pronouncing letters in a word and errors in reading vowels mark (harakat). This research focuses on finding the pronunciation characteristics of students' reading Arabic texts and this is a novelty in this research. It is hoped that this research can provide good solutions and concepts in the implementation of qira'ah learning in senior high schools in the future.